Postural and gait abnormalities in a group of Romney lambs due to pain induced by severe chronic cutaneous dermatophilosis. Issue 1 (2nd January 2022) - Champion, CP; Bycroft, K; Castillo-Alcala, F; Collett, MG
ABSTRACT: Case history: Fifteen lambs from a flock of 1, 000, 5-month-old Romney lambs in the Manawatū region of New Zealand, developed unusual postural and gait abnormalities during the summer of 2020. In mid-January, the lambs were grazing a raphanobrassica crop ( xRaphanobrassica; Brassica oleracea x Raphanus sativus ) but were removed from this crop soon after as they developed dermal lesions on the pinnae consistent with photosensitisation (colloquially known as "rape scald"). The lambs were placed onto a shaded paddock containing a pasture of predominantly perennial ryegrass ( Lolium perenne ) and white clover ( Trifolium repens ). One week following removal from the crop (late January), the 15 lambs developed abnormal postures and gaits that were described by farm staff as "neurological" and "swayback-like". Clinical findings: From a distance, all 15 lambs exhibited remarkably similar abnormal posture and gait whereby their weight was borne on their carpi, and they appeared to crawl while walking due to crouched hindquarters and prominent lordosis. Of the affected lambs, five were submitted for clinical examination. All five had normal vital signs. The results of neurological examinations were within normal limits. In response to palpation of the dorsum, the lambs performed an exaggerated and unusual dipping motion, particularly when pressure was applied over the lumbar spine. Parting of the fleece over the dorsum revealed thickened, indurated skin that cracked and tore easily. Pathological findings: The shorn pelt of a euthanised lamb revealed a large (100 cm × 40 cm), locally extensive, irregular ovoid region of the skin of the dorsum that was markedly thickened, indurated and crusted. Impression smears of the lesions revealed long filamentous chains of plump coccoid bacteria separated by transverse and longitudinal septa, consistent with Dermatophilus congolensis . Histopathology of the lesions revealed severe, chronic-active, locally extensive, necrosuppurative dermatitis with marked acanthosis, orthokeratotic and parakeratotic hyperkeratosis, ulceration, filamentous bacteria and coccoid zoospores. Diagnosis: Cutaneous dermatophilosis due to Dermatophilus congolensis . Clinical relevance: Painful dermal lesions due to severe dermatophilosis of the dorsal skin of sheep are capable of causing postural and gait abnormalities that may be misinterpreted as signs of neurological abnormality. Such dermal lesions may be concealed by an apparently normal fleece.